Analisis Rainbow Antimagic Coloring Pada Hasil Operasi Comb Graf Lintasan - Feby Suryandana (jcgant, 2021)
All the graphs in this paper are connected graphs. Let G=(V,E) where V(G) is a set of vertex from graph G while E(G) is a set of edge from graph G. A bijection function f: V → {1,2,3,...,V(G) vert} the associated weight of an edge uv E(G) under f is W_f(uv)=f(u)+f(v). A path P in a vertex-labeled graph G is said to be a rainbow path if for every two edges uv, u'v' E(P), there is w_f(uv)≠ w_fu'v'. If for every two vertices u and v of G, there is a rainbow u-v path, then f is called a rainbow antimagic labeling of G. A graph G is rainbow antimagic if G has a rainbow antimagic labeling. The minimum number of color needed to make G rainbow connected, called rainbow antimagic connection number, denoted by rac(G). In this paper, we will analyze the rainbow antimagic coloring on comb product of path graph.